THE USE OF ZIRCONIUM CEMENTS IN MEDICINE: PHYSICO-CHEMICAL PROPERTIES AND CLINICAL BENEFITS - Giuroiu Cristian Levente; Clara Haddad; Cristina Albert; Doina Spaiuc; Rusnac Roman; Cezarina Dragomirescu; Alexandru Patrascu; Alina Stefanache (Romanian Journal of Oral Rehabilitation)
Aim of the Study: Zirconium-containing cements are now an important material in restorative dentistry, providing improved mechanical properties, biocompatibility, and aesthetics, leading to their growing usage in dental practices. This research aims to examine all the physical and chemical characteristics of zirconium cements, including their structural strength, resistance to fractures, and durability against chemical degradation. Additionally, the study seeks to evaluate the medical advantages of zirconium cements, including their ability to provide long-lasting restorations, minimize problems like microleakage, and ensure a natural appearance that closely mimics the visual characteristics of tooth enamel. By examining these factors, the study aims to highlight how zirconium cements can improve the durability and effectiveness of dental repairs.